La rétention de particules par une éponge hexactinellide, Oopsacas minuta (Leucopsacasidae): Le rôle du reticulum. (Particle uptake by a hexactinellid sponge, Oopsacas minuta(Leucopsacasidae): the role of the reticulum) - Pérez, T. (Comptes-Rendus de l'Académie des Sciences de Paris, 1996)
The discovery of a hexactinellid sponge, Oopsacas minuta, in a Mediterranean submarine cave provided the opportunity to study its feeding strategy. Experimental particles (latex bends and bacteria) are retained by a kind of endopinacodenn peculiar to hexactinelLids, the reticuLum, which has a great ability of retention. The particle digestion is perftnned in this tissue. The choanocytes, responsible for the uptake of particLes in the Demospongiae and the CaLcarea, seem, in the Hexactinellida, to mainly provide the water circulation. A deveLoped aquiferous system and the retention ability ofthe hexactineilid are interpreted as an adaptation to a scarcity of particLes in deep sea